2, 4-Dihydroxy-3′-methoxy-4′-ethoxychalcone suppresses cell proliferation and induces apoptosis of multiple myeloma via the PI3K/akt/mTOR signaling pathway. (1st January 2019) - Zhu, FengChen; Jiang, DianMing; Zhang, MingHua; Zhao, Bo
Abstract: Context: Caragana pruinosa Kom. (Fabaceae), a commonly used folk medicine, has been found to possess antitumor effects. However, the antiproliferative effect of 2, 4-dihydroxy-3′-methoxy-4′-ethoxychalcone (DMEC) derived from C. pruinosa against multiple myeloma (MM) has never been investigated. Objective: This study systematically evaluates the antiproliferative effect of DMEC against MM cells. Materials and methods: The antiproliferative effect of DMEC (1, 2, 4, 8, 16, 32, and 64 μM) on MM cells lines, including RPMI8226, MM.1S, and U266, was examined using Cell counting kit-8 (CCK-8) assay after 24 h incubation. The proapoptotic effect of DMEC (20 μM) was determined using fluorescent microscope and flow cytometer, and its possible underlying mechanisms were further studied by using western blotting analysis. Results: The half maximal inhibitory concentrations (IC50 ) of DMEC on RPMI8226, MM.1S, and U266 cells were calculated as 25.97, 18.36, and 15.02 μM, respectively. The inhibitory effect of DMEC on MM cells was related to mitochondria-mediated apoptosis via upregulation of the cleaved-caspase-3 (C-3), cleaved-caspase-9 (C-9), Bad, and cytochrome C (Cyto C), but downregulation of the Bcl-2 and poly ADP-ribose polymerase (PARP). Furthermore, DMEC (5, 10, and 20 μM) reduced the expression of phosphatidylinositol-3-kinase (PI3K), phosphorylated (p)-protein kinase B (Akt), and p-mammalian target of rapamycin (p-mTOR), which were further evidenced by pretreatment with IGF-1, a PI3K activator. Conclusion: Collectively, our results indicate that the DMEC could be treated as a new candidate for treatment of multiple myeloma in the future. Also, an in vivo study is warranted in the future.